Thermal fatigue effects on the compressive strength and ultrasonic pulse velocity of rubber-based composite - Sakami, Siham; Elabbassi, Fatima-Ezzahra; Boukhattem, Lahcen; Abalouch, Ibtissam (AIP conference proceedings, 2023)
The present work is an attempt to partially replace the coarse aggregates in concrete by the rubber aggregates and to study their impact on mechanical properties of the obtained lightweight concretes. In fact, the rubber aggregates have less specific gravity and are available in huge amounts worldwide. To produce our lightweight concrete, we replaced coarse aggregates with rubber aggregates by varying the replacement proportion from 0% to 30% with increment of 10%. The obtained samples were subject to several heating / cooling cycles from 25 ° C up to 600 ° C. Then, the sonic auscultation, tensile and compressive tests were carried out to assess the effect of temperature variation on the mechanical properties.